Gutta percha A comparative study of three methods of obturation - Asuncion, Princesita M.; Cola, Ma. Luisa T.; Jimena, Edna M. (Adviser)+.
This study was done to compare three of the more commonly used and generally accepted gutta percha filling technique: Kloropercha infusion, vertical condensation with warm gutta percha and internal condensation in the basis of replication of the prepared root canal and its inherent merphologic abarrations. Eighty four extracted adult human teeth were selected for this study to determine which method replicated the entire prepared root canal system. Models for obsturated root canals were made by dissolving away the tooth structure. Based on the results, Kloropercha infusion technique proved to be best in replicating the prepared root canal system and its mephologic variations.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.